Novel OS for smart cities turns energy consumers into 'prosumers'. (Research'eu results magazine)
What's a smart city without smart people to run it? This question led the IURBAN consortium to develop a decision support system that collects and analyses energy consumption and production from the likes of power plants, EV charging stations and buildings. The new system is hoped to enable better management and planning in smart cities-with both producers and consumers being provided with just enough information to play their part.